2014
DOI: 10.1007/s10648-014-9261-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Traditional Bullying and Cyberbullying: Challenges of Definition and Measurement in Adolescents – a Review

Abstract: The need for an integrated approach to studying bullying behaviors, both traditional and cyber, in adolescents is increasingly evident. The definitional criteria of bullying are well established in the traditional bullying literature and include (i) intention, (ii) repetition, and (iii) power imbalance. There is emerging evidence that these same criteria can be broadly applied to cyberbullying behaviors; however, important additional elements may include anonymity and publicity in a cyber-act. Fundamental to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
173
1
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 229 publications
(198 citation statements)
references
References 80 publications
6
173
1
18
Order By: Relevance
“…Relational victimization is more strongly related to emotional distress than is physical victimization [2] and has been found to be uniquely predictive of social and psychological maladjustment as well as depression in adulthood [7], [8]. Victims of bullying have indicated that social exclusion was the worst form of bullying [2]; however, teachers tend to treat relational bullying as the least serious form [2], [3].…”
Section: A Types Of Victimizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Relational victimization is more strongly related to emotional distress than is physical victimization [2] and has been found to be uniquely predictive of social and psychological maladjustment as well as depression in adulthood [7], [8]. Victims of bullying have indicated that social exclusion was the worst form of bullying [2]; however, teachers tend to treat relational bullying as the least serious form [2], [3].…”
Section: A Types Of Victimizationmentioning
confidence: 99%
“…Finally, the recent explosion in the availability of electronic communication technologies has provided students with a new medium to bully [2], [9]. This form of bullying, known in the research as cyber bullying, includes bullying through e-mail, instant messaging, in a chat room, on a website, or through digital messages or images sent to one's phone [2], [10], [11].…”
Section: A Types Of Victimizationmentioning
confidence: 99%
See 3 more Smart Citations